Linia czasu - Crichton, Michael, 1942-2008; Leszczynski, Andrzej (Warszawa : Amber, 1999)
Polish translation of "Timeline". A time travel science fiction story about the past being actualized in the present.
Translation of: Timeline.
Includes bibliographical references.
Keywords: Twenty-first century -- Fiction; Quantum theory -- Fiction; Time travel -- Fiction; Historians -- Fiction; France -- History -- 14th century -- Fiction